Preface: 3rd International Symposium on Communication Engineering & Computer Science (CECS 2023) - Xu, Jianyu; William, Pearl (Transactions on Computer Science and Intelligent Systems Research, 2024)
This proceeding includes original and peer-reviewed research papers from the 3rd International Symposium on Communication Engineering & Computer Science (CECS 2023), which was held on December 30-31, 2023 in Wuhan, China. The conference is an international symposium for the presentation of technological advances and research results in the fields of communication engineering, computer science and related topics. The conference will bring together leading researchers, engineers and scientists in the domain of interest from around the world. We warmly welcome prospected authors submit their new research papers to this 3rd CECS and share the valuable experiences with the scientist and scholars around the world. CECS 2023 received 67 manuscripts. By submitting a paper to CECS 2023, the authors agreed to the review process and understood that papers undergo a peer-review process. Manuscripts were reviewed by appropriately qualified experts in the field selected by the Conference Committee, who gave detailed comments and-if the submission was accepted the authors would submit a revised version that considered this feedback. All papers were reviewed using a double-blind review process: authors declared their names and affiliations in the manuscript for the reviewers to see, but reviewers did not know each other’s identities, nor did the authors receive information about who had reviewed their manuscript. The Committees of CECS 2023 invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit. Hopefully, all participants and other interested readers will benefit scientifically from the proceedings and also find it stimulating in the process. Conference Organizing Chair Wuhan, China